Putative multiple alleles at the vegetative (heterokaryon) incompatibility loci het-c and het-8 in Neurospora crassa - B. J. Howlett; J. F. Leslie; D. D. Perkins (Fungal Genetics Reports, 1993)
It has never been determined in Neurospora whether multiple alleles exist at individual het loci such that interaction between any two unlike alleles will result in an incompatibility reaction. The evidence summarized here from recombination genetics and from sampling natural populations suggests multiple allelism at two of the best studied het loci. However, an alternate explanation is not excluded that invokes linked multiple loci rather than multiple alleles.